Compostos de coordenação entre os hexafluorofosfatos de lantanídeos (III) e o trimetilfosfato - Sousa, Evanise Frota de (1984)
This present research work is concerned with the and characterization the compounds obtained from the hexafluorophosphate of lanthanides(III) and the ligand trimethylphosphate (TMP). [...]